Molecular biology: Rap and chirp about X inactivation - Roth, Anna; Diederichs, Sven (Nature.com, 2015)
Two new techniques identify proteins that directly interact with a non-protein-coding RNA called Xist to mediate inactivation of one X chromosome in female mammals. See Letter p.232